HISTORY OF THE DEVELOPMENT OF THE OLYMPIC COMMITTEE OF UZBEKISTAN - Хамдамов Алишер Тохир угли (Journal Park Publishing, 2024)
This article is devoted to the history of the stage of development of the Olympic movement in the Republic of Uzbekistan. Reforms in the field of mass sports to attract people to mass sports.
Keywords: Olympic movement, mass sports, reform, Olympic Committee, history of development.